2013
DOI: 10.4103/0028-3886.125270
|View full text |Cite
|
Sign up to set email alerts
|

Cost of stroke from a tertiary center in northwest India

Abstract: Direct medical cost or acute care of stroke accounted for a major component of cost of stroke. Poor outcome, length of hospital stay, and higher income were the cost driving factors. The socioeconomic impact on the family decreased at follow up probably due to joint family system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…The common measure of OOPP was expenditure for per hospital stay or inpatient care or hospitalization cost per household member [ 24 , 25 , 34 , 35 , 38 ] while cost subdivided in terms of indirect cost, direct cost, non-medical cost or was calculated altogether [ 42 , 43 ]. OOPP as the proportion of total household spending [ 34 , 38 ] or perceived financial hardship by caretakers was also studied [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The common measure of OOPP was expenditure for per hospital stay or inpatient care or hospitalization cost per household member [ 24 , 25 , 34 , 35 , 38 ] while cost subdivided in terms of indirect cost, direct cost, non-medical cost or was calculated altogether [ 42 , 43 ]. OOPP as the proportion of total household spending [ 34 , 38 ] or perceived financial hardship by caretakers was also studied [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although eight papers met the selection criteria, these included a systematic review (Gheorghe et al, 2018), with only one study relevant to our scoping review (Huffman et al, 2011). A decision was made to exclude the systematic review and include only the relevant study (Huffman et al, 2011), resulting in eight studies being included in the scoping review (Bahuguna et al, 2020; Basu et al, 2015; Chhabra et al, 2019; Gopi et al, 2017; Huffman et al, 2011; Kwatra et al, 2013; Marfatia et al, 2014; Singla & Singla, 2016). Details of the records excluded following full-text screening (with related reasons) are presented in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were set in broad and specific geographical locations, ranging from the whole of India (n = 1 [Basu et al, 2015]) to specific states or regions-Delhi National Capital Region (n = 1 [Singla & Singla, 2016]) and Punjab, Haryana, Tamil Nadu, Odisha, Himachal Pradesh and Kerala (n = 1 [Bahuguna et al, 2020])-and cities, that is Guntur (n = 1 [Gopi et al, 2017]), Gurgaon, Mumbai and Bengaluru (n = 1 [Marfatia et al, 2014]), Trivandrum (n = 1 [Huffman et al, 2011]), Ludhiana (n = 1 [Kwatra et al, 2013]) and an unspecified location in Punjab (n = 1 [Chhabra et al, 2019]).…”
Section: Overall Summary Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this review will be reported in line with the PRISMA 2009 checklist. 28 The overall quality of evidence on outcomes will be presented using the GRADE (Grades of Recommendation, Assessment, Development and Evaluation) approach, 29 which involves consideration of within-study risk of bias (methodological quality), directness of evidence, heterogeneity, precision of effect estimates and risk of publication bias. We will rate overall quality of evidence at four levels: high, moderate, low and very low.…”
Section: Methods and Analysismentioning
confidence: 99%